The Apu Ausangate In Popular Narrative - Valderrama Fernández, Ricardo (1975)
The present selection of myths is a sample of the oral tradition collected in the communities of peasants and indigenous shepherds of the high provinces of Cusco and Apurímac. These myths belong to the community members of Lauramarca (Cusco) and were collected during the year 1973. Our thanks to Enrique Rosas P. for his collaboration in the translation.